Risk Factors for Pressure Injuries in Stroke Patients: A Systematic Literature Review - Chayati, Nur; Septari, Zhavira Nadya (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Stroke causes weakness in the limbs, which makes stroke patients often fall into bed rest. Continuous pressure on the skin and bone protrusions during bed rest can lead to decreased blood flow, tissue ischemia, and infection, which can result in pressure injury. Bedrest conditions will differ from one disease to another, with the highest incidence in stroke patients. Internal and external factors influence the risk of pressure ulcers and their severity. The study aims to analyze the risk factors for pressure injury in stroke patients. This literature review used two international databases PubMed and Science Direct, and other supporting literature from Google Scholar. The keywords pressure injury, risk factors, and stroke were used. The articles were published between 2016 and 2021. The quality of the articles was examined using the Joanna Briggs Institute Review Instrument. The results show pressure injuries in stroke patients arise from the combined effects of immobility, moisture, compromised nutritional status, and sensory impairment. Prolonged inability to change body position contributes to sustained pressure, reduced tissue perfusion, and increased vulnerability of the skin, while moisture associated with incontinence promotes maceration and disrupts epithelial integrity. Pressure injuries are a serious problem in stroke patients, especially those who are on bed rest. Providing education and counseling, as well as assistance to families, should be carried out, using interesting media and paying attention to every risk factor for pressure injuries.